Clinical management of six cases of low-risk primary tonsillar non-Hodgkin´s lymphoma - Colleoni, Gisele Wally Braga; Oliveira, José Salvador Rodrigues; Alves, Antonio Correa; Borducchi, Davimar Miranda Maciel; Segreto, Roberto Araújo; Cervantes, Onivaldo; Kerbauy, José (São Paulo Medical Journal, 1999)
CONTEXT: There have been many reports that favor aggressive systemic treatment with chemotherapy and radiotherapy, even for well-localized lymphomas, avoiding the need for tonsillectomy of the normal tonsil. CASE REPORT: We report six cases of primary tonsillar lymphoma with a median patient age of 42 years. There were two lymphoma cases with diffuse large cells, two cases with mixed small and large cells, one with small cells and one indeterminate. They were treated with six cycles of chemotherapy and cervical radiotherapy. All patients achieved durable complete remission. Our data agree with previous reports that suggested that primary tonsillar high-grade B-cell NHL has a good prognosis if aggressively treated.